Socialization of Mobile Phone Utilization for Simple Bookkeeping Practices for Micro and Small Businesses in Responding to Government Programs - Sugiartiningsih, Sugiartiningsih; Suparjiman; Ahmad Diponegoro; Yuti Yuniarti; Arief Yunan; Iis Dewi Fitriani; Helin Garlinia Yudawisastra; Risma Fauziah (IMPACTS: International Journal of Empowerment and Community Services, 2025)
ABSTRACT The inability of Micro, Small and Medium Enterprises (MSMEs) to prepare financial reports is caused by low knowledge and mixing of personal and business finances. Therefore, it is necessary to introduce simple bookkeeping practices through the SIAPIK program in collaboration between Muhammadiyah University of Bandung and Bank Indonesia West Java. Objective: The objective of this Community Service (PkM) is to improve the ability of simple bookkeeping for MSMEs through the SIAPIK program, so that they can prepare accurate and effective financial reports. Method: The method used in this PkM is a qualitative approach with lectures and training on the use of mobile phones to apply SIAPIK to trade cases, especially the fashion business in Bandung. The training was carried out in four phases, namely: (1) installing SIAPIK on mobile phones, (2) inputting initial data, (3) transactions, and (4) displaying reports. Results: The results of the training showed that the activities went smoothly and MSME actors in Antapani District were satisfied with being able to practice the four phases directly guided by Bank Indonesia West Java officers and the assistants involved. The success of this PkM activity is proven by the highest score on the assessment questionnaire for the indicators of presenters, materials, and facilities and infrastructure that obtained good results. Thus, this PkM can improve simple bookkeeping skills for MSEs and help them in preparing accurate and effective financial reports. Keywords: financial report, SIAPIK, mobile phone, bookkeeping